PEMBELAJARAN TOLERANSI DALAM BUKU AJAR PAI TINGKAT SEKOLAH DASAR - Putri Utami Asrianti, - (2023)
This research attempts to put forward the learning of tolerance in Islamic Religious Education textbooks at the Elementary School (SD) level. The purpose of this research is to: (1) Describe the proportion of the scope of PAI material in PAI textbooks for grades I to VI at the elementary level; (2) Describe how tolerance learning materials are contained in Islamic Education textbooks for grades I-VI at the elementary school level. This study uses a literature study with a qualitative approach that analyzes the contents of textbooks published by the Ministry of Education and Culture for the Revised 2013 Curriculum (Classes II, III, V, and VI) and the Merdeka Curriculum (Classes I and IV). The data obtained was then collected and analyzed using the content analysis method. Data analysis techniques in this study used 3 data analysis steps, namely: data reduction, data display, and data verification. This study found that the proportion of the scope of PAI material is more dominant in the scope of morality by 25% when viewed from the number of chapters, and 29.4% seen from the number of CP or KD. As for the PAI textbooks for classes I-VI, there are 77 contents of tolerance material which include: (1) Tolerance in carrying out each other's beliefs and worship; (2) tolerance in living side by side with other religions; (3) Tolerance in relations between public relations; and (4) tolerance in the internal relations of Muslims with a larger portion in textbooks that already refer to the independent curriculum.